Correlation between platelet‐derived growth factor‐B gene polymorphism and coronary heart disease - Lu, Yaru; Liu, Hui; Dong, Bo; Yang, Jingyu; Kou, Lu; Qin, Qin (Journal of clinical laboratory analysis, 2022)
Object The aim of the present work was to investigate the correlation of plasma platelet‐derived growth factor (PDGF)‐BB level and single nucleotide polymorphism (SNP, rs1800817 and rs2285094) of PDGF‐B gene with the onset and stability condition of coronary heart disease (CHD). Methods Totally, 335 subjects were included in and divided into CHD (n = 247) and control group (n = 88) according to coronary angiography. Besides, the patients in the CHD group were divided into acute coronary syndrome (ACS) group (n = 165) and stable angina pectoria (SAP) group (n = 82), based on CHD stability condition. The plasma PDGF‐BB level was measured by ELISA, and the genotype of PDGF‐B was examined through qPCR assay. Results The PDGF‐BB level was positively correlated with hsCRP level (r = 0.149, p < 0.05). The genotype frequencies of SNP rs1800817 and rs2285094 match Hardy–Weinberg equilibrium. There was weak linkage disequilibrium between SNP rs1800817 and rs2285094: D′ = 0.419, r2 = 0.04, which has no correlation with CHD. There was no statistical difference in plasma PDGF‐BB level among different genotypes in rs1800817 and rs2285094. There were no differences in the plasma PDGF‐BB level among patients with any genotype of SNP rs1800817 and rs2285094, no matter how it was grouped. Logistic regression results indicated that the plasma PDGF‐BB level was the independent risk factor of CHD onset (OR = 1.003, 95% CI 1.001–1.006, p = 0.014). Conclusions High plasma PDGF‐BB level is the risk factor of CHD and has correlation with instability of CHD. The plasma PDGF‐BB level change may be related to inflammatory response. PDGF‐B gene rs1800817 and rs2285094 polymorphisms are not correlated with CHD. Research Process and Results.